The Age of Empathy : NATURE'S LESSONS FOR A KINDER SOCIETY - Waal, Frans De, 1948- (Frans B. M.) (London : Souvenir Press, 2019)
Greed is out, empathy is in. Human empathy has the backing of a long evolutionary history. Can studying the role of empathy in evolution among animals help to build a just society based on the more generous elements of human nature? Is evolutionary biology the force behind the sense of social responsibility and community building that are the keynotes of Obama's political vision and David Cameron's 'Big Society' as they lead us into a new Age of Empathy? Written accessibly, with an incisive intelligence and humour, providing a wealth of anecdotes and scientific examples, The Age of Empathy is essential reading to understand how evolutionary biology can change our society.
Originally published: London : Souvenir Press, 2010.
Includes references pages and index
Keywords: Empathy; Empathy -- Social aspects; Social behavior in animals; Emotions; Emotions in animals; Helping behavior; Altruistic behavior in animals